Space, Power, and The Politics of Fixity: A Critique of The Nile and Indian Ocean as Transboundary Categories - Musenze, Junior Brian (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
The conceptual categories of the Nile River and the Indian Ocean have historically been treated as timeless, fixed geographical truths. This rarely contested assumption stems from mainstream historiography, which privileges written records and is essentially Western in its orientation. This dominant narrative typically traces the Nile from a singular point, such as Egypt, and similarly provincializes India in the Indian Ocean discourse, effectively silencing indigenous African actors in the interoceanic space. This article argues that such historiography, which attempts to provincialize specific geographical categories and impose a hegemonic Western power structure upon them, is insufficient for explaining the complex dynamics of space and power prior to Western hegemony. Despite the apparent fixity of these two aquatic spaces, they contain alternative, suppressed, or denied definitions that persist through the epistemological protest of oral literacy and tradition. By conceptualizing space before Western hegemony, this study offers an alternative framework for understanding issues of identity that are often narrowly defined by the modern state